Denmark : Financial System Stability Assessment-Press Release; and Statement by the Executive Director for Denmark. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Much of the work of the Financial Sector Assessment Program (FSAP) was conducted prior to the COVID-19 pandemic. Given the FSAP's focus on medium-term challenges and vulnerabilities, however, many of its findings and recommendations for strengthening policy and institutional frameworks remain pertinent. This report reflects key developments and policy changes since the FSAP mission work was completed, and includes illustrative scenarios to quantify the possible implications of the COVID-19 shock on the solvency of systemically important financial institutions (SIFIs). Prior to the COVID-19 pandemic, the Danish authorities had taken important steps to improve financial system resilience. The authorities had actively used macroprudential tools to bolster the robustness of the financial system. The supervision of the banking and insurance sectors had improved. Likewise, recent legislation has strengthened anti-money laundering and combating the financing of terrorism (AML/CFT) supervision. Major reforms such as a new bank resolution framework had also considerably improved Denmark's financial safety net and crisis management frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet